Penerapan Aplikasi Inventory Barang dengan Menggunakan Extreme Programming Pada Perusahaan Manufaktur - Loisa, Julia; Zefanya Ivgantius, Titus Zefanya; Fernandes Andry, Johanes (KALBISCIENTIA Jurnal Sains dan Teknologi, 2020)
Today’s technology continues to grow rapidly because of the function of the technology itselfthat can help users manage a data faster. Thus the application of a system becomes a natural thing ifthe company wants to increase sales of products it has created. Manufacture Company is a companythat produces liquid fertilizer which is then sold to consumers. But in terms of recording the availabilityof goods as well as recording sales transactions are still done manually, it will eventually affect thecompany because of the increasing market demand. Therefore an inventory application system was builtto accommodate this. This application is designed with the main goal of making it easier for workersto record the availability of goods and sales transactions to be more systematic. This application willbe created using Visual Basic programming language and has a database server, MySQL. The methodused to design this application uses SDLC Extreme Programming. This application is expected to beable to simplify the process of recording an item, both material received from suppliers and the resultsof production, as well as produce a better sales report than previously done manually.